Comparison of Two Toric IOLs with Different Haptic Design: Optical Quality after 1 Year. (11th February 2018) - Miháltz, Kata; Lasta, Michael; Burgmüller, Michael; Vécsei-Marlovits, Pia Veronika; Weingessel, Birgit
Abstract : Background. The purpose of this prospective, randomised study was to interocularly compare the visual performance after implantation of two different toric IOLs with different haptic design. Methods. 59 subjects with corneal astigmatism greater than 1.25 diopter (D) were implanted with an AT TORBI 709M IOL (Carl Zeiss Meditec AG) in one eye and with a Tecnis toric aspheric IOL (Abbot Medical Optics) in the other eye. Observation procedure was performed 12 months postoperatively. Main outcome measures included uncorrected distance visual acuity (UDVA), manifest refraction, IOL rotation, and IOL position. Results. Mean UCDVA was 0.04 ± 0.14 logMAR for AT TORBI eyes and 0.06 ± 0.15 logMAR for Tecnis eyes (p = 0.3 ). The postoperative spherical equivalent values were significantly lower in the AT TORBI group. Mean toric IOL axis rotation was 3.0 ± 2.26 degrees for AT TORBI eyes and 3.27 ± 2.37 for Tecnis eyes (p = 0.5 ). The mean vertical IOL tilt and vertical decentration values measured with the Visante OCT were significantly larger in the AT TORBI group (p < 0.05 ). Conclusions. Both the Tecnis and the AT TORBI toric IOLs successfully reduced ocular astigmatism. Emmetropia could be better achieved with the AT TORBI IOL, whereas the Tecnis showed better positional stability. This trial is registered with ICMJENCT03371576 .